2022
DOI: 10.3390/polym14153074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Marker Materials and Spectroscopic Methods for Tracer-Based Sorting of Plastic Wastes

Abstract: Plastics are a ubiquitous material with good mechanical, chemical and thermal properties, and are used in all industrial sectors. Large quantities, widespread use, and insufficient management of plastic wastes lead to low recycling rates. The key challenge in recycling plastic waste is achieving a higher degree of homogeneity between the different polymer material streams. Modern waste sorting plants use automated sensor-based sorting systems capable to sort out commodity plastics, while many engineering plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Figure 1 shows a possi ble decision tree for the selection of potential mark ers, which was developed in more detail within the research project "PLASTMARK". 26,27 Detection methods for TBS Spectroscopic detection methods have long been used to identify and separate different materials. Mechanical recycling facilities for used plastics primarily use NIR sensors.…”
Section: Tracer-based Sorting (Tbs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a possi ble decision tree for the selection of potential mark ers, which was developed in more detail within the research project "PLASTMARK". 26,27 Detection methods for TBS Spectroscopic detection methods have long been used to identify and separate different materials. Mechanical recycling facilities for used plastics primarily use NIR sensors.…”
Section: Tracer-based Sorting (Tbs)mentioning
confidence: 99%
“…54,55 Figure 1: Proposed decision tree for the selection of marker materials that would be considered for specific plastic streams. 26…”
Section: Tracer-based Sorting (Tbs)mentioning
confidence: 99%
“…38,40,42−44 However, in their current states, both Raman and MIR are impractical for independent use in large-scale sorting operations. 45 A combination of NIR and factor analysis has demonstrated some ability to distinguish between various classes of POs, including HDPE and LDPE blends. 41,46,47 Additionally, both Kim et al and Sato et al have demonstrated that partial least-squares regression (PLSR) of NIR spectra may be able to predict properties such as densities, crystallinity, and melting points of PEs made by a single manufacturer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Even hyperspectral imaging, an extremely data-rich technique, struggles to distinguish the subtle shifts between subclasses of PE . The use of multiple spectroscopic methods, such as NIR or Fourier transform infrared (FTIR) and Raman measurements, coupled with multivariate data analysis has been shown to identify key properties such as density and crystallinity in POs. ,, FTIR/mid-IR (MIR) can use peak ratios to provide a quantitative value for the branching content, which can then be used to infer trends in crystallinity and density. ,, However, in their current states, both Raman and MIR are impractical for independent use in large-scale sorting operations . A combination of NIR and factor analysis has demonstrated some ability to distinguish between various classes of POs, including HDPE and LDPE blends. ,, Additionally, both Kim et al and Sato et al have demonstrated that partial least-squares regression (PLSR) of NIR spectra may be able to predict properties such as densities, crystallinity, and melting points of PEs made by a single manufacturer. , However, in both papers, the authors appear to use manufacturer-provided properties and assume they remain constant despite thermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…TBS can be done in several ways. One option is applying fluorescent tracer materials and using a corresponding detection unit ( Olscher et al, 2022 ). Another option is the use of digital watermarks, i.e., codes that are integrated into the design of the packaging and can be detected by cameras on high-speed sorting lines ( De Tandt et al, 2021 ; Lange, 2021 ).…”
Section: Introductionmentioning
confidence: 99%